The Stateless Nation’s Elite: Artistic Collections of Polish Aristocracy, 1795–1918 - Kłudkiewicz, Kamila; Mencfel, Michał (Acta historiae artis Slovenica, 2023)
The article aims to investigate aristocratic collecting practices in the former Polish-Lithuanian Commonwealth in the 19th century, focusing on three points. First, we highlight the specific situation of the Polish aristocracy compared to most European countries and note the weakness of collecting culture in the Polish-Lithuanian Commonwealth in the early modern period, followed by its slow emergence at the end of the 18th century. Then, we investigate the most important phenomena of 19th-century aristocratic collecting and distinguish two major trends within it: collecting art and collecting national memorabilia. We also highlight the importance of aristocratic collections for a stateless nation. Finally, to illustrate the overview, using a specific example to underline the key issues, we discuss the collections of Princes Czartoryski. In this essay, we summarize our previous research on the collections of Polish aristocracy and provide, for the first time, a comprehensive and systematic panorama of this phenomenon.